Concentraciones de Nutri-compost en las características agronómicas y rendimiento de Lactuca sativa L. lechuga, variedad Mónica SF 31, Loreto.2025 - Diaz Navarro, Norma Felicita (2025)
The study was carried out in Loreto, in an area dedicated to crop production, south of Iquitos, whose coordinates in UTM were from 9676245 North and 693266 South. The objective was to demonstrate the action of Nutri-compost in the cultivation of lettuce variety Monica SF 31. Loreto. The DBCA experimental design was used with four Blocks, the results of which led to the following conclusions: The application of Nutri compost in the T4 has an important effect on the weight (350 g) and total width of the lettuce plant variety Monica SF 31, located in the Loreto region. The concentration of 40 t/ha of Nutri-compost (T4) was found to be the most efficient in terms of maximizing the width (44 cm) and total weight of the vegetable (350 g), indicating the effectiveness of Nutri-compost in the crop.